3(x-4x+2)-(3x-16)=0

Simple and best practice solution for 3(x-4x+2)-(3x-16)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x-4x+2)-(3x-16)=0 equation:


Simplifying
3(x + -4x + 2) + -1(3x + -16) = 0

Reorder the terms:
3(2 + x + -4x) + -1(3x + -16) = 0

Combine like terms: x + -4x = -3x
3(2 + -3x) + -1(3x + -16) = 0
(2 * 3 + -3x * 3) + -1(3x + -16) = 0
(6 + -9x) + -1(3x + -16) = 0

Reorder the terms:
6 + -9x + -1(-16 + 3x) = 0
6 + -9x + (-16 * -1 + 3x * -1) = 0
6 + -9x + (16 + -3x) = 0

Reorder the terms:
6 + 16 + -9x + -3x = 0

Combine like terms: 6 + 16 = 22
22 + -9x + -3x = 0

Combine like terms: -9x + -3x = -12x
22 + -12x = 0

Solving
22 + -12x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-22' to each side of the equation.
22 + -22 + -12x = 0 + -22

Combine like terms: 22 + -22 = 0
0 + -12x = 0 + -22
-12x = 0 + -22

Combine like terms: 0 + -22 = -22
-12x = -22

Divide each side by '-12'.
x = 1.833333333

Simplifying
x = 1.833333333

See similar equations:

| X+2.9=9.1 | | 5(2x-9)-8x+35=120 | | 0.5(x-2)-(0.3x-16)=0 | | (D^3+3D^2-4D)y=0 | | v^2-7v+11=0 | | 3y-y+4y=12 | | 6(z+2)-2(2z+5)= | | 121x^2-154x+49=0 | | 12x+2(x-3)=5(2x-1)+7 | | 5x-6=-4(3-x) | | 225x^2-81=0 | | 225x^2-81=0 | | 2x+15=3-x | | u^2+9u-3=0 | | 5h+2(11-h)-5= | | 4(4y-1)+3-2(3+y)=0 | | -3(4-6y)+7(-y+5)=-8 | | (a+6)(a*2-8a+8)= | | 6c^2+7cd-5d^2= | | 2(x+3)-3x=5-x+1 | | 2x+5+6x-20=180 | | 8x-2(x+5)=5(2x-6) | | 9x-3y=27 | | 6a-47-2a=8a-15 | | 6x-5=-2x+11 | | 3(x+4)-2(x-1)=4(x+4) | | 75-3n+6n=12+15n-2+3n+20 | | -5+3m=3-m | | -3(-2)+6+-2= | | -1+3(x-1)=8x-5(x-2)-14 | | 7x-40-27x=10x+6+36 | | x^2+18x+53=594 |

Equations solver categories